Polymorphism of inflammatory system genes in the pathogenesis of rheumatic heart disease - A. V. Sinitskaya; M. V. Khutornaya; M. Yu. Sinitsky; O. N. Khryachkova; M. A. Asanov; A. V. Ponasenko (Российский кардиологический журнал, 2022)
Aim. To assess the contribution of polymorphic variants of inflammatory response genes to the predisposition to rheumatic heart disease.Material and methods. Using real-time polymerase chain reaction, we analyzed the prevalence of 18 polymorphic variants of 8 genes involved in the inflammatory process in 251 patients with rheumatic heart disease and 300 healthy donors.Results. We found that homozygous TT genotypes of rs1800871 (IL10) (p=0,02) and TT rs1800872 (IL10) polymorphisms (p=0,027), as well as TT genotypes of CRP gene (rs1205) (p=0,015) and GG genotypes of rs375947 (IL12RB) (p=0,037) are "risky" and associated with the development of rheumatic heart disease.Conclusion. Associations of polymorphic variants rs1800871 and rs1800872 of the IL10 gene, rs1205 of the CRP gene, and rs375947 of the IL12RB gene can be an important link in the pathogenesis of rheumatic heart disease and can later be used as biological markers for a personalized assessment of the disease risk.